Study the Effect of Two Fungi Metarhizium anisopliae M, Beauveria bassiana Vand the Pesticide ICON onLarvae, Pupa and Adult House Fly Musca domestica L - Gharib, Waleed Ibrahim; Abd-Ali, Maki Hamed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A study was conductedto determine thethe effects of two insect pathogenic fungiMetarhizium anisopliae and Beauvaria bassiana In biological control and comparing, insecticide, Icon, on larva , pupa and adults stage of house fly  was tested. The results  revealed non-significantly superiority differences in the percentages of cumulative death between the recommended concentration of Icon and the M.anisopliae(2 Ã— 1011), but the results showed, significant difference in accumulation death between M. anisoplia ( 2 Ã— 1011 ) and  B. bassiana were found at the same concentration, the accumulation death of  M.anisoplia reached to 100, 80, 95% for larval, pupa and stage after 96  hours respectively,  compared with  the accumulation death of B. bassiana  ( 2 Ã— 1011 ), 77.5, 70,82.5%, after 96hours respectively.The pesticide showedA significant impact on the larval and adult as the ratio of the cumulative death reached two phases of 100% after 24 hours of treatment,While the pesticide did not show a significant impact in the pupa stage as mortality rate reached 5% at this stage after 96 hours of treatment, possibly due to the nature of the pupa that do not feed as in the larval and adult